Assessment of the natural bed of Gracilaria heteroclada (Zhang et Xia) in Jaro, Iloilo - Luhan, Ma. Rovilla J. (College of Fisheries, U. P.in the Visayas, 1991)
The study was conducted to determine the seasonality of biomass, reproductive states, and agar quality of Gracilariaheteroclada and the effect of the different environmental factors on this parameters. Biomass was collected using a quadrat, plants were sectioned to determine population fertility, and agar was analyzed using the method of Nelson et al. (1983).Peak biomass in February (45 g/m2) and lowest in July (1.16 g/m2) revealed biomass seasonality in the area. Fertile plants were also seasonal with highest carposporophyte occurrence in January 48%) and low the rest of the year ; and highest tetrasporophyte occurrence in May (64%) and low the rest of the year. Gel strength and yield were negatively correlated. Good agar quality occurred during dry season and poor quality during wet season.